Push-pull type bis(dialkoxythienyl)ethylene chromophore compound and composite material, film and optoelectronic integrated device containing the same
Through the combination of push-pull bis(dialkoxythienyl)ethylene chromophore compound and polymer, the problems of low electro-optical coefficient and poor thermal stability of electro-optical materials are solved, and efficient electro-optical performance improvement and film-forming quality improvement are achieved. , suitable for the large-area preparation of electro-optical modulators and information technology applications.
Patent Information
- Application Number
- CN202110829120.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-21
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-07-21
AI Technical Summary
Existing organic electro-optical materials face the problems of low electro-optical coefficient, poor solubility, low thermal stability and poor film formation quality, which limits the performance of electro-optical modulators and large-area preparation applications.
Using push-pull bis(dialkoxythienyl)ethylene chromophore compound, the band gap of the chromophore and the combination of π-electron donor groups and conjugated bridge groups and π-electron acceptor groups are adjusted. Nonlinear optical properties, improve electro-optical coefficient and thermal stability, and mix with polymer to make composite materials to improve film formation quality.
It significantly improves the electro-optical coefficient and thermal stability of electro-optical materials, enhances the optical quality of film formation, and is suitable for large-area preparation and next-generation information technology applications.
Smart Images

Figure CN115677678B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical materials, and in particular to a push-pull type bis(dialkoxythienyl)ethylene conjugated bridge dipole chromophore compound and a composite material, a film and an optoelectronic integrated device containing the same. Background Art
[0002] Electro-optic or electro-absorption modulators are devices that modulate laser intensity by voltage. Organic electro-optic materials are important for modulating electrical signals. Existing electro-optic materials face problems such as low electro-optic coefficient, poor solubility, low thermal stability and poor film quality.
[0003] Organic electro-optical materials have the advantages of solution processing and easy structural adjustment. The optical waveguide material obtained by blending organic small molecule chromophores with organic polymers can be used to make complex optoelectronic integrated devices through processes such as spin coating, photolithography or imprinting, and can be mass-produced. Chromophore compounds are often limited by low electro-optic coefficients. The donor-conjugated bridge-acceptor (D-π-A) structural modification method is the simplest and most effective method to improve the electro-optic coefficient of the chromophore. Among them, the conjugated bridge has the functions of connecting the donor and the acceptor, increasing the conjugation length of the chromophore, improving the thermal stability of the chromophore, and increasing the dipole moment and hyperpolarizability. How to simply and efficiently modify the conjugated bridge and improve the electro-optic coefficient is of great significance to the development of electro-optical materials. It has broad potential for realizing large-scale preparation, assembly and application of modulators, as well as next-generation information technology applications. Summary of the invention
[0004] In order to solve the above technical problems, the first object of the present invention is to provide a push-pull type bis(dialkoxythienyl)ethylene chromophore compound.
[0005] The second object of the present invention is to provide a composite material containing the above chromophore compound.
[0006] The third object of the present invention is to provide a film made of the above composite material, and an optoelectronic integrated device having the film.
[0007] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0008] The present invention provides a push-pull type bis(dialkoxythienyl)ethylene chromophore compound, which comprises a π-electron donor group, a conjugated bridge group and a π-electron acceptor group; the general structural formula of the chromophore compound is shown in Formula 1:
[0009] R1-R2=R3 Formula 1;
[0010] In Formula 1, R1 is a π-electron donor group, which is N,N-dialkylaminobenzene, and its structure is shown in Formula 2:
[0011]
[0012] R4 in Formula 2 is selected from a C1-12 alkyl group;
[0013] R2 is a conjugated bridge, and its structure is shown in Formula 3:
[0014]
[0015] R5 in Formula 3 is selected from a C1-12 alkyl group;
[0016] R3 is a π-electron acceptor group selected from tricyanofuran (TCF) derivatives, dicyanothiazole, dicyanoindanone and tricyanophthalamide, and its structure is selected from Formula 4-7:
[0017]
[0018] R6 and R7 in Formula 4 are independently selected from -CF3, phenyl or substituted phenyl, and the substituted phenyl is preferably a phenyl substituted with a para-halogen, more preferably a p-fluorophenyl;
[0019] According to the chromophore compound of the present invention, Formula 4 is preferably the following structure:
[0020]
[0021] Those skilled in the art will appreciate that in the above structural formula The chemical bonds are the connecting bonds between the groups.
[0022] In the chromophore compound provided by the present invention, the π-electron donor group is conjugated with the π-electron acceptor group of different structures through the bis(dialkoxythienyl)ethylene conjugated bridge group. By changing the electron-withdrawing ability of the π-electron acceptor and adjusting the push-pull strength of the donor-acceptor, the band gap of the chromophore is adjusted, so that the chromophore has different nonlinear optical properties.
[0023] According to the chromophore compound of the present invention, the conjugated bridge is a bis(dialkoxythienyl)ethylene group, and its structure is shown in Formula 3. Preferably, R5 in Formula 3 is selected from a C2-6 alkyl group; for example, in a specific embodiment of the present invention, R5 can be an n-butyl group. The bis(dialkoxythienyl)ethylene conjugated bridge has a long conjugation length, connects the donor and the acceptor, and increases the dipole moment length of the chromophore. Moreover, the chromophore needs to be processed into a film later, and the chromophore needs to have good solubility; because the main chain structure is an aromatic conjugated structure, it has high rigidity and poor solubility. The four n-butyl chains of the conjugated bridge can significantly improve the solubility of the chromophore, photochemical stability, easy solvent processing and improve the optical quality of the film. However, if the R5 alkyl chain is too long, the molecular weight of the chromophore will be increased, and the molar concentration of the chromophore will be reduced at the same mass ratio, which is not conducive to improving the electro-optical coefficient.
[0024]
[0025] According to the chromophore compound of the present invention, the π-electron donor group is an N,N-dialkylaminobenzene donor unit, which has a strong electron donating ability; its structure is shown in Formula 2, preferably, R4 is selected from a C1-4 alkyl group; for example, in a specific embodiment of the present invention, R4 can be an ethyl group.
[0026]
[0027] According to the chromophore compound of the present invention, the π-electron acceptor group is a tricyanofuran (TCF) derivative, dicyanothiazole, dicyanoindanone or tricyanophthalamide, and its structure is shown in Formula 4-7:
[0028]
[0029] According to the chromophore compound of the present invention, preferably, the structural formula of the chromophore compound is one of the following formulae:
[0030]
[0031] The above chromophore compound provided by the present invention is a nonlinear optical material and can be used to prepare optical composite materials, optical films, electro-optical devices and the like.
[0032] The present invention also provides a synthetic route of more than one chromophore compound:
[0033]
[0034] Wherein, R4, R5, R6, and R7 are as defined above.
[0035] A second aspect of the present invention provides a composite material comprising the above chromophore compound.
[0036] According to the composite material of the present invention, preferably, based on the total weight of the composite material, the mass ratio of the chromophore compound is 10%-30%.
[0037] According to the composite material of the present invention, preferably, the composite material further comprises a polymer. The chromophore compound of the present invention is mixed with a polymer to prepare a composite material, which has the advantages of being easy to process into a film and having a large nonlinear coefficient.
[0038] According to the composite material of the present invention, preferably, the polymer comprises one or a combination of two or more of polymethyl methacrylate, methyl methacrylate-styrene copolymer and polycarbonate. More preferably, the present invention adopts methyl methacrylate-styrene copolymer.
[0039] According to the composite material of the present invention, preferably, within the wavelength range of 1000nm-1600nm, the electro-optic coefficient r of the composite material is 33 15pm / V to 80pm / V.
[0040] According to the composite material of the present invention, preferably, under the action of an electric field of 0-40 V / μm, within a wavelength range of 1000 nm-1600 nm, a change value of the refractive index of the composite material is 0.0005 to 0.004.
[0041] The electro-optic coefficient r 33 The change values of refractive index are obtained by making the composite material into a thin film and then testing it.
[0042] The third aspect of the present invention provides a film made of the above composite material.
[0043] The present invention also provides an optoelectronic integrated device, which has the above-mentioned thin film. Preferably, the optoelectronic integrated device is an electro-optical device. The chromophore provided by the present invention realizes a relatively large electro-optical effect.
[0044] Electro-optic modulators are devices that modulate laser intensity by voltage. Organic electro-optic materials play an important role in electro-optic signal modulation. Existing electro-optic materials face problems such as low electro-optic coefficient, low thermal stability and poor film quality. The present invention uses a bis(dialkoxythienyl)ethylene conjugated bridge connected to receptors with different electron donating abilities, so that the electro-optical performance, stability and processability of the material are significantly improved. It has broad potential for realizing large-scale preparation, assembly and application of modulators, as well as next-generation information technology applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 The compound BTVFPTCF of Example 1 1 H NMR results.
[0046] Figure 2 This is the HRMS (ESI) m / z result of the compound BTVFPTCF in Example 1.
[0047] Figure 3 The compound BTVCF3TCF of Example 2 1 H NMR results.
[0048] Figure 4 This is the HRMS (ESI) m / z result of the compound BTVCF3TCF in Example 2.
[0049] Figure 5 The compound BTVBTM of Example 3 1 H NMR results.
[0050] Figure 6 HRMS (ESI) m / z result of compound BTVBTM of Example 3.
[0051] Figure 7 The compound BTVCNI of Example 4 1 H NMR results.
[0052] Figure 8 This is the HRMS (ESI) m / z result of the compound BTVCNI of Example 4.
[0053] Fig. 9 For compound 7 of Example 5 1 H NMR results.
[0054] Fig.10 For compound 7 of Example 5 13 C NMR results.
[0055] Fig.11 The compound BTVTCP of Example 5 1 H NMR results.
[0056] Fig.12 This is the HRMS (ESI) m / z result of the compound BTVTCP in Example 5.
[0057] Fig.13 The compound BTVTCF of Comparative Example 1 1 H NMR results.
[0058] Fig.14 This is the HRMS (ESI) m / z result of the compound BTVTCF of Comparative Example 1.
[0059] Fig.15The cyclic voltammetry curves of the compounds of Examples 1-5 and Comparative Example 1 in tetra-n-butylammonium hexafluorophosphate / dichloromethane solution are shown.
[0060] Fig.16 This is the molar extinction coefficient spectrum of the compound FBTVTCF of Comparative Example 1 in solution.
[0061] Fig.17 This is a molar extinction coefficient spectrum of the compound BTVFPTCF of Example 1 in solution.
[0062] Fig.18 This is the molar extinction coefficient spectrum of the compound BTVCF3TCF of Example 2 in solution.
[0063] Fig.19 This is a molar extinction coefficient spectrum of the compound BTVBTM of Example 3 in solution.
[0064] Fig. 20 This is a molar extinction coefficient spectrum of the compound BTVCNI of Example 4 in solution.
[0065] Fig.21 This is a molar extinction coefficient spectrum of the compound BTVTCP of Example 5 in solution.
[0066] Fig. 22 It is the pure film absorption coefficient spectrum diagram of the compounds of Examples 1-5 and Comparative Example 1.
[0067] Fig.23 This is a graph showing the test results of TE and TM wave reflection intensity of a film made of a mixture of the compound BTVCF3TCF in Example 2 and a polymer at a wavelength of 1304 nm for an unpolarized film and a polarized film. DETAILED DESCRIPTION
[0068] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0069] All numerical specifications herein (e.g., temperature, time, concentration, and weight, etc., including ranges for each thereof) are generally approximate values that may be appropriately varied (+) or (-) in increments of 0.1 or 1.0. All numerical specifications may be understood as being preceded by the term "about."
[0070] The structure of compound 1 in the following examples is as follows:
[0071]
[0072] The preparation process of compound 1 refers to the synthesis methods of Jin D, Londongan T, Huang D, et al. Achieving large electro-optic response: DH-type chromophores in both crosslinked systems and linear high-Tg systems [C] / / Organic Photonic Materials and Devices VI. International Society for Optics and Photonics, 2004, 5351: 44-56. and Huang, Diyun, et al. "Systematic study of electro-optic materials composed of non-linear optical chromophores and polycarbonates." Optoelectronic Materials and Devices for Optical Communications. Vol. 6020. International Society for Optics and Photonics, 2005.
[0073] Example 1
[0074] This example prepares a chromophore compound (compound BTVFPTCF), the structure of which is shown below:
[0075]
[0076] The synthetic route is as follows:
[0077]
[0078] In a flask, compound 1 (0.12 g, 0.18 mmol), compound 2 (70 mg, 0.19 mmol), pyridine (56 μL, 0.70 mmol), 4 mL of ethanol, and 4 mL of chloroform were added and refluxed overnight. After 2 days of reaction, silica gel was added, the solvent was evaporated, and the mixture was passed through a column with n-hexane:ethyl acetate (volume ratio 4:1) (118 mg, 65.7%).
[0079] The compound BTVFPTCF 1 The H NMR test results are as follows: Figure 1 As shown:
[0080] 1 H NMR(300MHz,Chloroform-d)δ7.69(d,J=15.4Hz,1H),7.41–7.29(m,6H),7.24–7.13(m,5H),7.03(d, J=16.0Hz,1H),6.86(d,J=15.9Hz,2H),6.67(d,J=8.6Hz,2H),6.56(d,J=15.4Hz,1H),4.16(q,J=6.8 Hz,4H),4.04(t,J=6.6Hz,2H),3.96(t,J=6.6Hz,2H),3.42(q,J=7.0Hz,4H),1.83–1.71(m,6H),1.58 –1.44(m,8H),1.34(d,J=7.7Hz,2H),1.21(t,J=7.0Hz,6H),1.05–0.98(m,9H),0.91(t,J=7.3Hz,3H).
[0081] The compound BTVFPTCF(C 60 H 64 F2N4O5S2Na + (M+Na) + ) HRMS (ESI) m / z calculated value is 1045.41784, and the measured value is 1045.41760. The specific results are as follows Figure 2 shown.
[0082] Example 2
[0083] This embodiment provides a chromophore compound (compound BTVCF3TCF), the structure of which is shown below:
[0084]
[0085] The synthetic route is as follows:
[0086]
[0087] In a flask, compound 1 (0.15 g, 0.22 mmol), compound 3 (104 mg, 0.33 mmol), 4 mL of ethanol, and 4 mL of chloroform were added and refluxed overnight. Silica gel was added, the solvent was evaporated, and the mixture was passed through a column with n-hexane: dichloromethane (volume ratio 1:2) (181 mg, 84.2%).
[0088] The compound BTVCF3TCF 1 The H NMR test results are as follows: Figure 3 As shown:
[0089] 1H NMR(300MHz,Chloroform-d)δ7.84(d,J=15.3Hz,1H),7.60–7.31(m,8H),7.04(d,J=16. 0Hz,1H),6.93–6.83(m,2H),6.73–6.63(m,2H),6.55(d,J=15.2Hz,1H),4.18(t,J=6.6H z,4H),4.04(t,J=6.6Hz,2H),3.98(t,J=6.6Hz,2H),3.42(q,J=7.1Hz,4H),1.86–1.71( m,6H),1.68–1.60(m,2H),1.56–1.26(m,8H),1.21(t,J=7.0Hz,6H),1.07–0.93(m,12H).
[0090] The compound BTVCF3TCF(C 55 H 61 F3N4O5S2Na + (M+Na) + ) HRMS (ESI) m / z calculated value is 1001.39277, and the measured value is 1001.39301. The specific results are as follows Figure 4 shown.
[0091] Example 3
[0092] This example prepares a chromophore compound (compound BTVBTM), the structure of which is shown below:
[0093]
[0094] The synthetic route is as follows:
[0095]
[0096] In a flask, compound 1 (100 mg, 0.15 mmol), compound 4 (45 mg, 0.22 mmol), sodium acetate (24 mg, 0.29 mmol), 1 mL of acetic anhydride were added and kept at 90°C overnight. n-hexane was added, the liquid was poured out, the solid was taken out, and it was purified by column with dichloromethane:ethyl acetate (volume ratio 30:1) (17.4 mg, 17.1%).
[0097] The compound BTVBTM 1 The H NMR test results are as follows: Figure 5 As shown:
[0098] 1H NMR(300MHz,Chloroform-d)δ8.27(s,1H),7.44–7.30(m,3H),7.12–6.91(m,2H),6.86 (d,J=16.0Hz,1H),6.68(d,J=8.5Hz,2H),4.34(t,J=6.4Hz,2H),4.20(t,J=6.6Hz,2H) ,4.05(td,J=6.6,4.1Hz,4H),3.42(q,J=7.0Hz,4H),1.80(dpd,J=10.0,6.7,3.3Hz,8H ),1.61(d,J=3.6Hz,2H),1.58–1.48(m,6H),1.21(t,J=7.0Hz,6H),1.12–0.95(m,12H).
[0099] The compound BTVBTM (C 49 H 64 N4O4S3Na + (M+Na) + ) HRMS (ESI) m / z calculated value is 891.39819, and the measured value is 891.39850. The specific results are as follows Figure 6 shown.
[0100] Example 4
[0101] In this example, a chromophore compound (compound BTVCNI) was prepared, and its structure is shown below:
[0102]
[0103] The synthetic route is as follows:
[0104]
[0105] In a flask, compound 1 (150 mg, 0.22 mmol), compound 5 (64 mg, 0.33 mmol), pyridine (67 mg, 0.44 mmol), and 10 mL of chloroform were added, and the mixture was refluxed at 60°C for 2 days. The solvent was dried, and silica gel was added, and the mixture was passed through a column with n-hexane: dichloromethane (volume ratio 1:1) (167 mg, 88.6%).
[0106] The compound BTVCNI 1 The H NMR test results are as follows: Figure 7 As shown:
[0107] 1H NMR(300MHz,Chloroform-d)δ9.09(s,1H),8.73–8.60(m,1H),7.89(dd,J=6.7,2.0Hz,1H),7.78–7.66(m,2H),7.57(d ,J=15.9Hz,1H),7.38(d,J=8.6Hz,2H),7.13–6.94(m,2H),6.88(d,J=16.0Hz,1H),6.68(d,J=8.4Hz,2H),4.40(t,J=6 .9Hz,2H),4.19(t,J=6.8Hz,2H),4.06(td,J=6.6,2.5Hz,4H),3.42(q,J=7.0Hz,4H),1.84(dddt,J=24.7,12.3,9.1,6 .8Hz,8H),1.62(dd,J=7.4,2.0Hz,1H),1.53(ddd,J=16.6,8.5,6.5Hz,7H),1.21(t,J=7.0Hz,6H),1.12–0.96(m,12H).
[0108] The compound BTVCNI (C 51 H 60 N3O5S2 + (M+H) + ) HRMS (ESI) m / z calculated value is 858.39689, and the measured value is 858.39709. The specific results are as follows Figure 8 shown.
[0109] Example 5
[0110] This example prepares a chromophore compound (compound BTVTCP), the structure of which is shown below:
[0111]
[0112] The synthetic route is as follows:
[0113]
[0114] Step V, synthesis of compound 7:
[0115] In a flask, compound 1 (150 mg, 0.22 mmol), compound 6 (45 mg, 0.33 mmol), and 2 ml of ethanol were added and reacted at 80°C for 3 days. The solvent was dried, silica gel was added, and the mixture was purified by column chromatography using n-hexane:ethyl acetate (volume ratio 4:1) (92 mg, 52.3%).
[0116] The compound 7 1 The H NMR test results are as follows: Fig. 9 As shown:
[0117] 1 H NMR(400MHz,Chloroform-d)δ8.35(s,1H),7.52–7.30(m,3H),7.03(d,J=16.0Hz,1H),6 .88(dd,J=21.2,16.0Hz,2H),6.68(d,J=8.6Hz,2H),6.16(s,2H),4.31(t,J=6.7Hz,2H) ,4.17(t,J=6.6Hz,2H),4.04(dt,J=10.2,6.6Hz,4H),3.42(q,J=7.1Hz,4H),1.80(tdd, J=11.7,8.3,6.3Hz,8H),1.64–1.46(m,8H),1.21(t,J=7.0Hz,6H),1.10–0.94(m,12H).
[0118] The compound 7 13 The C NMR test results are as follows. The specific spectrum is as follows Fig.10 As shown:
[0119] 13 C NMR (101MHz, CDCl3) δ165.08,158.64,150.65,147.75,146.24,145.63,141.53,14 0.86,129.75,129.15,128.12,123.96,123.69,120.92,116.44,116.29,115.14,11 3.65,113.08,111.64,89.37,74.77,74.65,73.98,73.76,51.11,44.46,32.11,32.07,32.04,31.89,29.73,19.24,19.22,19.03,13.96,13.95,13.92,13.88,12.69.
[0120] Step ⅵ, synthesis of compound BTVTCP:
[0121] In a flask, compound 7 (78 mg, 0.1 mmol), compound 8 (44 mg, 0.3 mmol), triethylamine (42 μl, 0.3 mmol), and 4 ml of dry dichloromethane were added and reacted at room temperature for 15 hours. The solvent was dried, silica gel was added, and purified by column chromatography using dichloromethane: ethyl acetate (volume ratio 30:1) (54 mg, 58.1%).
[0122] The compound BTVTCP 1The H NMR test results are as follows: Fig.11 As shown:
[0123] 1 H NMR(300MHz,Chloroform-d)δ8.38(s,1H),8.05(dd,J=5.6,3.1Hz,2H),7.90(dd,J=5.5,3.1Hz,2H),7.47 (d,J=15.7Hz,1H),7.38(d,J=8.7Hz,2H),7.04(d,J=16.0Hz,1H),6.91(dd,J=15.9,10.3Hz,2H),6.68(d, J=8.8Hz,2H),4.37(t,J=6.6Hz,2H),4.18(t,J=6.7Hz,2H),4.03(td,J=6.6,5.1Hz,4H),3.42(q,J=7.0Hz ,4H),1.90–1.70(m,8H),1.58–1.39(m,8H),1.21(t,J=7.0Hz,6H),1.00(ddt,J=16.8,10.5,7.4Hz,12H).
[0124] The compound BTVTCP (C 53 H 60 N5O6S2 + (M+H) + ) HRMS (ESI) m / z calculated value is 926.39795, and the measured value is 926.39777. The specific results are as follows Fig.12 shown.
[0125] Comparative Example 1
[0126] This comparative example prepared a chromophore compound (compound BTVTCF), the structure of which is shown below:
[0127]
[0128] The synthetic route is as follows, and the synthetic steps refer to Example 1.
[0129]
[0130] The compound BTVTCF 1 The H NMR test results are as follows: Fig.13 As shown:
[0131] 1H NMR(300MHz,Chloroform-d)δ7.89(d,J=15.6Hz,1H),7.38(d,J=8.6Hz,2H),7.27–7. 16(m,1H),7.10–6.79(m,3H),6.68(d,J=8.4Hz,2H),6.49(d,J=15.6Hz,1H),4.32(t, J=6.5Hz,2H),4.17(t,J=6.7Hz,2H),4.04(td,J=6.6,4.9Hz,4H),3.42(d,J=7.3Hz,4 H),1.89–1.72(m,14H),1.59–1.46(m,8H),1.21(t,J=7.0Hz,6H),1.08–0.97(m,12H).
[0132] The compound BTVTCF (C 50 H 62 N4O5S2Na + (M+Na) + ) HRMS (ESI) m / z calculated value is 885.40538, and the measured value is 885.40570. The specific results are as follows Fig.14 shown.
[0133] Test Example 1
[0134] The compounds obtained in Examples 1-5 and Comparative Example 1 were subjected to cyclic voltammetry tests, using 0.1 M tetra-n-butylammonium hexafluorophosphate / dichloromethane as the electrolyte, a platinum wire electrode as the working electrode, a platinum sheet electrode as the counter electrode, Ag / AgCl as the reference electrode, and ferrocene for calibration. Fig.15 Table 1 summarizes the cyclic voltammetry results and absorption results. Fig.15 It can be seen that this type of material has a reversible redox peak, showing a reversible redox process. Due to the presence of the same donor group, the HOMO energy level of the chromophore changes very little, from about -4.87eV to -4.91eV, and due to being connected to receptors with different electron-withdrawing abilities, the LUMO energy level of the chromophore changes greatly.
[0135] The LUMO energy level of the chromophore BTVTCF in comparative example 1 is -3.74eV. When the acceptor is changed to FP-TCF, the LUMO energy level of BTVFPTCF is reduced to -3.82eV. When the acceptor is changed to CF3-TCF with stronger electron-withdrawing ability, the LUMO energy level of BTVCF3TCF is further reduced to -3.93eV. The electrochemical band gap is reduced from 1.13eV in comparative example 1 to 1.05eV for BTVFPTCF and 0.96eV for BTVCF3TCF, respectively. When the acceptor is replaced by dicyanothiazole or tricyanophthalamide from TCF derivatives, the electrochemical band gaps of BTVBTM and BTVTCP are significantly reduced to 1.09eV and 1.03eV, respectively.
[0136] Table 1 Cyclic voltammetry results of chromophores and summary of absorption results
[0137]
[0138] Test Example 2
[0139] The compounds obtained in Examples 1-5 and Comparative Example 1 were subjected to absorption spectrum test using UV-vis-NIR absorption spectrum test. The compounds in Examples 1-5 and Comparative Example 1 were diluted to a concentration of 1×10 -5 The solution of M, the solvents are 1,4-dioxane, trichloroethylene, chloroform, dichloromethane, cyclohexanone, acetone, and dimethyl sulfoxide (DMSO); the test is carried out using a 1 cm quartz cuvette at room temperature. The extinction coefficient (ε) of the material is calculated using the formula: A = εcb, where A is the absorbance of the maximum absorption peak; c is the material concentration; and b is the thickness of the cuvette used. Figure 16-Figure 21 This is the result of the extinction coefficient. The compound is dissolved in chloroform and spin-coated on glass to form a thin film, called a pure film. The thickness of the film is tested by a step profiler, and the absorption coefficient is calculated by measuring the absorbance of the maximum absorption peak. The absorption coefficient is calculated according to the formula: A = lgT = Kbc, where A is the absorbance of the maximum absorption peak, T is the transmittance, K is the absorption coefficient, b is the thickness, and c is the concentration. Fig. 22 is the normalized absorption coefficient result of the pure film. Figure 16-Figure 21 It can be seen that this type of material shows strong vis-NIR Absorption and Solvatochromism.
[0140] The maximum absorption wavelength of the chromophore of Comparative Example 1 in chloroform is 725nm, and the optical band gap is 1.30eV. The electron-withdrawing ability of the acceptor is enhanced, and the TCF is changed to FP-TCF, and the absorption wavelength of BTVFPTCF in chloroform is red-shifted by 51nm, and further enhanced to CF3-TCF, BTVCF3TCF in chloroform is red-shifted by 120nm. The optical band gap is also reduced from 1.30eV to 1.14eV and 1.08eV, respectively, which shows the same trend as the electrochemical test results. Similarly, the acceptor is replaced by TCF derivatives with dicyanothiazole or tricyanophthalamide, and the maximum absorption wavelengths of BTVBTM and BTVTCP in chloroform are red-shifted by 56nm and 99nm, respectively, and the electrochemical reduction is reduced to 1.16eV and 1.09eV.
[0141] Test Example 3
[0142] The prism-coupled waveguide refractive index test was performed on the compound BTVCF3TCF of Example 2, wherein the incident wavelength was 1304 nm.
[0143] Test method references Wang, W.; Wu, J.; Chen, K.; Huang, Q.; Luo, J.; Chiang, KS, Graphene electrodes for electric poling of electro-optic polymer films. Optics Letters, 2020, 45, 2383-2386. Kuzyk, MG and CWDirk, Characterization Techniques and Tabulations for Organic Nonlinear Optical Materials.1998:Marcel Dekker.
[0144] The chromophore compound is mixed with the polymer methyl methacrylate-styrene copolymer in a certain proportion (the chromophore compound accounts for 10-30wt%), dibromomethane is added to fully dissolve and mix, and then spin-coated on ITO glass. After vacuum drying, it is processed and tested. The film thickness is tested using a step meter. Gold plating is used as the positive electrode, ITO is used as the negative electrode, and an electric field (100V / μm) is applied. The temperature is increased, and when it rises to the glass transition temperature range of 95-110°C, the leakage current increases significantly, indicating that the polarization is successful, and the temperature is lowered and cooled. The prism coupling used is a commercial prism coupling tester, model 2010 / M, produced by Metricon, USA.
[0145] Test results such as Fig.23 As shown in Table 2 and Table 3. Fig.23The polarized film of BTVCF3TCF contains 14.80% chromophore, which is equivalent to a number density N of 1.0×10 20 cm -1 , at 1304nm laser wavelength, the reflection intensity test results of TE and TM waves on the unpolarized film and polarized film respectively. Fig.23 It can be seen that after polarization, the TE and TM refractive indices of the polarized film change, and TM is significantly greater than TE after polarization. Table 2 shows the test results of the prism-coupled waveguide refractive index of the polarized film of compound BTVCF3TCF at 1304nm. When a certain voltage is applied, the refractive index of the compound changes significantly (under the action of an electric field of 0-30.2V / μm, the change in the refractive index at a wavelength of 1304nm is 0.0036), which shows that the compound BTVCF3TCF of Example 2 has a good electro-optical effect.
[0146] Table 3 summarizes the electro-optical performance results of Examples 1-5 and Comparative Example 1. The chromophore BTVTCF of Comparative Example 1 has a number concentration of 1.0×10 20 cm -1 When the electro-optic coefficient (r 33 ) is 24.5pm / V. After enhancing the electron-withdrawing ability of the acceptor, the electro-optic coefficient of BTVFPTCF increases to 39.6pm / V. When replaced with CF3-TCF with stronger electron-withdrawing ability, the electro-optic coefficient of BTVCF3TCF is 59.8pm / V, which is 2.4 times that of comparative example 1. The hyperpolarizability reflects the potential of the chromophore in the field of electro-optical applications. The hyperpolarizability of BTVTCF in comparative example 1 is 1785×10 -30 esu, the hyperpolarizability of BTVCF3TCF is 4752×10 -30 esu is 2.7 times that of comparative example 1. Experiments show that when N,N-dialkylaminobenzene is used as a donor and bis(dialkoxythienyl)ethylene is used as a conjugated bridge, the electron-withdrawing ability of the acceptor is enhanced, and the electro-optical properties of the chromophore can be significantly improved.
[0147] Table 2 Test results of the refractive index of the prism-coupled waveguide at 1304 nm for the polarized film of compound BTVCF3TCF
[0148]
[0149] Table 3 Different chromophore compounds at number density N of 1.0×10 20 cm -1 The maximum absorption wavelength λ max (with polymer blend film), electro-optic coefficient (r 33 ), order parameter (Φ) and hyperpolarizability (β μ )
[0150]
[0151] The chromophore compound of the present invention uses a dialkyloxythienylethylene as a conjugated bridge, and the band gap of the chromophore is adjusted by adjusting the electron-withdrawing ability of the acceptor. When the acceptor is CF3-TCF, the band gap is the smallest and the electro-optic coefficient is the highest. For BTVCF3TCF, a large linear electro-optic coefficient (r 33 ), the number concentration is 1.0×10 20 mL -1 The electro-optic coefficient is 59.8pm / V, which is about twice that of the 30pm / / V of the commercial inorganic electro-optic crystal lithium niobate and more than twice that of BTVTCF.
[0152] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A push-pull type bis(dialkoxythienyl)ethylene chromophore compound, the structural formula of the chromophore compound is one of the following formulas:
2. A composite material comprising the chromophore compound according to claim 1.
3. The composite material according to claim 2, wherein: The content of the chromophore compound is 10%-30% based on the total weight of the composite material.
4. The composite material according to claim 2, wherein The composite material also includes a polymer.
5. The composite material according to claim 4, wherein The polymer includes one or a combination of two or more of polymethyl methacrylate, methyl methacrylate-styrene copolymer and polycarbonate.
6. The composite material according to claim 2, wherein: In the wavelength range of 1000nm-1600nm, the electro-optic coefficient r of the composite material is 33 15pm / V to 80pm / V.
7. The composite material according to claim 2, wherein: Under the action of an electric field of 0V-40V / μm, within a wavelength range of 1000nm-1600nm, the change value of the refractive index of the composite material is 0.0005 to 0.
004.
8. A film made of the composite material according to any one of claims 2 to 7.
9. An optoelectronic integrated device comprising the thin film according to claim 8.
10. The electrical integrated device according to claim 9, wherein: The optoelectronic integrated device is an electro-optical device.
Citation Information
Patent Citations
Second order nonlinear optical chromophores, polymers containing same, and electro-optic devices therefrom
CN1829939A